Combination therapy of hypertension in the elderly: a subgroup analysis of the Combination of OLMesartan and a calcium channel blocker or diuretic in Japanese elderly hypertensive patients trial - Ogihara, Toshio (Hypertens Res, 2015)
Combination of OLMesartan and a calcium channel blocker or a diuretic in Japanese elderly hypertensive patients (COLM) trial demonstrated that olmesartan combinations with a CCB or diuretic have similar effects on reducing cardiovascular risk in elderly hypertensive patients. However, the safety profiles suggest that olmesartan combined with CCB may be preferable to olmesartan combined with diuretic. In this subgroup analysis, we further evaluated the effects and safety of these combinations in elderly (65–74 years old (y.o.)) and very elderly (75–84 y.o.) hypertensive patients. In the COLM trial, 5141 patients (2918 elderly and 2223 very elderly) were randomly assigned to receive olmesartan-based therapy with either CCB or diuretic. The hazard ratios and 95% confidence intervals, respectively, in the elderly age group and in the very elderly group were: 1.04 (0.72–1.50; olmesartan plus CCB vs. olmesartan plus diuretic, P=0.85) and 0.71 (0.51–0.99, P=0.045) for the primary composite end point, and 1.07 (0.67–1.72, P=0.77) and 0.64 (0.42–0.98, P=0.036) for the composite of hard end points. The hazard ratios for stroke (fatal and non-fatal) were 1.48 (0.88–2.48; olmesartan plus CCB vs. olmesartan plus diuretic, P=0.13) and 0.63 (0.39–1.02, P=0.059) (interaction-P=0.019). Withdrawal rates from the trial, withdrawal due to serious adverse event and the incidence of any adverse event were higher in the olmesartan plus diuretic group than in the olmesartan plus CCB group in both age groups. In conclusion, angiotensin receptor blocker (ARB) and CCB combination may be preferable to an ARB and diuretic combination in the very elderly hypertensive patients for the reduction of cardiovascular risk, particularly for the reduction in stroke risk.